2016
DOI: 10.1038/srep20259
|View full text |Cite
|
Sign up to set email alerts
|

Organization of descending neurons in Drosophila melanogaster

Abstract: Neural processing in the brain controls behavior through descending neurons (DNs) - neurons which carry signals from the brain to the spinal cord (or thoracic ganglia in insects). Because DNs arise from multiple circuits in the brain, the numerical simplicity and availability of genetic tools make Drosophila a tractable model for understanding descending motor control. As a first step towards a comprehensive study of descending motor control, here we estimate the number and distribution of DNs in the Drosophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
150
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(163 citation statements)
references
References 93 publications
(133 reference statements)
10
150
3
Order By: Relevance
“…The present experiments provide further support for the generality of feeding control systems between insects and mammals [27,28]. Serotonin and octopamine were investigated as possible modulatory neurohormones based on a recent paper of Hsu and Bhandawat [29] on the organization of descending neurons in Drosophila melanogaster . The brain–gut axis is an essential part of the feeding control circuit in both mammals [2,30] and insects [8], especially when it comes to nutrient sensing [17,31].…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…The present experiments provide further support for the generality of feeding control systems between insects and mammals [27,28]. Serotonin and octopamine were investigated as possible modulatory neurohormones based on a recent paper of Hsu and Bhandawat [29] on the organization of descending neurons in Drosophila melanogaster . The brain–gut axis is an essential part of the feeding control circuit in both mammals [2,30] and insects [8], especially when it comes to nutrient sensing [17,31].…”
Section: Introductionmentioning
confidence: 68%
“…Thus, D . melanogaster possesses a complex serotonergic system featuring all major genes for 5-HT synthesis, metabolism and signaling [29] and provides a good model to test the effect of 5-HT on this important organ system.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from these cells, little is known of the roughly 1100 cells descending from the brain to the VNC [30]. Two noteworthy exceptions are the so-called “moonwalker neuron”, which elicits backward walking [31] and the giant fiber neuron, which triggers evasive take-offs [16].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other motor control centers (Jefferis et al, 2007;Tanaka, Awasaki, Shimada, & Ito, 2004;Travagli, Hermann, Browning, & Rogers, 2006), the CoGs integrate sensory information from various modalities, including mechanoand proprioceptive sensory structures Smarandache & Stein, 2007), and descending command signals from the brain (Hedrich & Stein, 2008). This is in contrast to many sensory neuropils and motor centers, which have rather consistent anatomical features across individuals of the same species or even between related species (Brandt et al, 2005;Burrows, 1996;Hsu & Bhandawat, 2016). This is in contrast to many sensory neuropils and motor centers, which have rather consistent anatomical features across individuals of the same species or even between related species (Brandt et al, 2005;Burrows, 1996;Hsu & Bhandawat, 2016).…”
Section: The Commissural Ganglia: Centers For Controlling Divergentmentioning
confidence: 99%
“…In some invertebrates, this applies even to the level of individual cells, providing detailed maps of the locations of identified neurons or classes of neurons and how they are clustered (Borst, 2014;Brandt et al, 2005;Burrows, 1996;Busch, Selcho, Ito, & Tanimoto, 2009;Hsu & Bhandawat, 2016;Jefferis et al, 2007;Wolff, Iyer, & Rubin, 2015). Analyses of neuropilar projection patterns and soma locations in a number of systems have demonstrated that sensory and motor structures in the brain are highly organized, and preserved across individuals of a given species.…”
Section: Introductionmentioning
confidence: 99%